Erratum to the article: “Energy intensity of hydrocarbons in liquid and solid states” - article Editorial (Тонкие химические технологии, 2021)
Gennady J. Kabo, Lubov A. Kabo, Larisa S. Karpushenkava, Andrey V. Blokhin  The original article can be found under https://doi.org/10.32362/2410-6593-2021-16-4-273-286